Highway 6: A Barrier to Wildlife Movement? - Coulson, Soren; Fedoriuk, Terry; Jannati, Mahshid; Wallace, Elizabeth (Prepared by the McMaster Research Shop for The Cootes to Escarpment Ecopark System, 2019)
Roads have been cited as a major disturbance to ecosystems by disrupting habitat and limiting wildlife movement. The cumulative negative effects of roads on local wildlife has been associated with an increase in species extinction. Highway 6 is a multi-lane urban highway that cuts through the Cootes to Escarpment EcoPark system and may be negatively impacting local wildlife. The purpose of this report is to answer the following research question: is Highway 6 a physical barrier to wildlife movement? A team of McMaster Research Shop Research Associates answered this question by conducting a literature review consisting of peer-reviewed publications, municipal reports, and books, as well as by performing site visits.
Keywords: Cootes Paradise; Wildlife corridor; Species migration; Habitat fragmentation; Hamilton; Community-based Research